Model for estimating the energy yield of a high concentrator photovoltaic system. (1st July 2015) - Fernández, Eduardo F.; Pérez-Higueras, P.; Almonacid, F.; Ruiz-Arias, J.A.; Rodrigo, P.; Fernandez, J.I.; Luque-Heredia, I.
Abstract: The prediction of the energy yield of HCPV (high concentrator photovoltaic) systems is crucial to evaluate the potential and promote the market expansion of HCPV technology. Currently, there is a lack of experience in the modelling of these kinds of systems due to the special features of such technology. In this work, a practical model based on simple mathematical expressions and atmospheric parameters is introduced. The proposed model takes into account the main important parameters which influence the output of a HCPV system such as cell temperature, spectrum and efficiency of the inverter and other losses of the BOS (balance of system). The results obtained are validated using the data of a HCPV installation located at the University of Jaen in southern Spain and monitored daily every minute since 2011. The model accurately predicts the monthly energy yield with a deviation ranging from 4.07% to −0.47% and the annual final energy yield with a deviation of 0.9%. Highlights: The prediction of the energy output of HCPV systems is a crucial task. A new model based on simple mathematical relationships is introduced. The procedure is validated using the measured data of a typical HCPV system. The analysis of results demonstrates the high quality of the methodology.